In the Shade of the Mango Trees. Border(s), Race and Nation in the Dominican Republic - Bourgeois, Catherine (2023)
This work offers a critical analysis of the applications of the notions of borders, race and nation in the Dominican Republic. It is based on a socio-anthropological study, with a historical and contemporary approach, carried out in the northern zone of the Haitian-Dominican border between 2007 and 2021. This article describes and analyzes the process of construction of the Dominican nation on the border and its relationship with Haiti. It also analyzes the anti-Haitian nationalist discourse and its historical and current effects on Dominican immigration policies, as well as its effects on the lives of thousands of migrants, and Dominicans of Haitian descent.